Seismic capacity of irregular unreinforced masonry buildings with timber floors. Issue 6 (7th June 2021) - Trutalli, Davide; Marchi, Luca; Scotta, Roberto; Pozza, Luca
Abstract : The in-plane stiffness of single straight-sheathed timber floors is normally supposed to be not sufficient to confer suitable seismic behaviour to the building. However, accurate evaluations of the in-plane behaviour of timber diaphragms and the effects of their deformability on the building response are difficult, especially for unreinforced masonry (URM) buildings. Various stiffening interventions of floors are possible; among them, the use of an additional layer of boards at 45° often demonstrates optimal behaviour as it combines the advantages of partial stiffening with minimum mass increase. This work was focused on the experimental characterisation of a stiff timber floor through cyclic loading testing of a three-dimensional full-scale specimen. The effects of in-plane flexibility and the non-linear behaviour of floors on the global response of URM buildings were evaluated by analysing the response of two buildings: a regular building and a building irregular in both plan and elevation. Analyses were conducted using a non-linear macro-element model to simulate the non-linear behaviour of masonry and the hysteretic behaviour of floors. The results showed that the seismic capacity of an URM building may be worsened by excessive stiffening of floors and/or mass increase.